Enhanced interannual variability of the terrestrial carbon sink in China under high emissions - Han Wu; Li Zhang; Honglin He; Xiaoli Ren; Mengyu Zhang; Dingjin Chu; Yuanhao Zheng (Environmental Research Letters)
Interannual variability (IAV) of terrestrial carbon uptake is a major contributor to the variation of atmospheric CO _2 . With the influence of the East Asian monsoon, future climate variability would significantly increase in China. However, how these future changes will modulate the IAV of China’s terrestrial carbon sinks remains unclear. Here, we analyzed the IAV of China’s terrestrial net ecosystem productivity (NEP _IAV ) and investigated the potential impacts of climate change under various scenarios during the 21st century using the outputs from nine Coupled Model Intercomparison Project Phase 6 models. The results reveal that China’s terrestrial NEP _IAV would be enhanced under higher emissions scenarios from 2015 to 2100. The standard deviation of national NEP _IAV under the SSP585 scenario rises by 12% compared with SSP126. The most prominent contribution to this enhancement in the total NEP _IAV comes from a larger NEP IAV in summer (10%), particularly in the subtropical–tropical monsoonal climate zone in China. Moreover, the enhancement is largely attributed to the intensified IAV in temperature and precipitation in the monsoonal climate zones as well as the heightened sensitivity to them, especially in the ecosystems of the subtropical–tropical monsoonal zone. Compared with monsoonal precipitation, IAV of temperature in the subtropical–tropical monsoonal climate zone also plays an important role in NEP _IAV under higher emissions scenarios. Our results highlight the crucial influence of future fluctuations in monsoon climate systems on terrestrial carbon sink IAV and the urgency of reducing the uncertainties of Earth system models in predicting both climate in monsoon regions and the responses of carbon cycling processes to temperature.